Implementation of the Caliphate Values in Tidal Flood Mitigation in Sayung District: An Environmental Ethics Approach Based on the Qur'an - Amalia, Zulfa; Sya'roni, Mokh. (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
This study aims to analyze the application of the concept of khalifah in tidal flood (rob) mitigation in Sayung District, Demak Regency, using the Living Qur'an approach as an environmental ethics foundation. The main focus of this research is to understand how the concept of khalifah is integrated into community-based mitigation practices to address the increasingly severe issue of rob. This study employs a descriptive-analytical qualitative method, with data collected through in-depth interviews with religious leaders, village officials, and affected residents, as well as direct observation of mitigation actions. The findings show that the value of khalifah, which emphasizes human responsibility as stewards of the earth, is implemented through collective actions such as community cooperation, mangrove planting, and housing adaptation. The study also provides recommendations for integrating religious values into the planning of community-based disaster mitigation policies in coastal areas. Penelitian ini bertujuan untuk menganalisis penerapan nilai khalifah dalam mitigasi banjir rob di Kecamatan Sayung, Kabupaten Demak, dengan menggunakan pendekatan Living Qur'an sebagai dasar etika lingkungan. Fokus utama penelitian ini adalah untuk memahami bagaimana konsep khalifah diintegrasikan dalam praktik mitigasi berbasis komunitas untuk mengatasi masalah rob yang semakin intensif. Penelitian ini menggunakan metode kualitatif deskriptif-analitis, dengan pengumpulan data melalui wawancara mendalam dengan tokoh agama, perangkat desa, serta masyarakat terdampak, serta observasi langsung terhadap tindakan mitigasi yang dilakukan. Hasil penelitian menunjukkan bahwa nilai khalifah, yang menekankan tanggung jawab manusia sebagai pengelola bumi, diimplementasikan dalam bentuk tindakan kolektif seperti gotong royong, penanaman mangrove, serta adaptasi rumah. Penelitian ini juga memberikan rekomendasi untuk mengintegrasikan nilai-nilai keagamaan dalam perencanaan kebijakan mitigasi bencana berbasis masyarakat di wilayah pesisir.